Does Intraoperative Fibrinogen Affect Blood Loss or Transfusion Practice After Aortic Arch Surgery: A Prematurely Ended Randomized Trial. (December 2022) - Vlot, Eline A.; Hackeng, Christian M.; Aper, Stijn J.A.; Sonker, Uday; Heijmen, Robin H.; van Dongen, Eric P.A.; Noordzij, Peter G.
Cardiovascular surgery is often complicated by significant bleeding due to perioperative coagulopathy. The effectiveness of treatment with fibrinogen concentrate to reduce the perioperative blood transfusion rate after thoracic aortic replacement surgery in prior studies has shown conflicting results. Therefore, we conducted a double-blind randomized controlled trial to investigate if a single dose of intraoperative fibrinogen administration reduced blood loss and allogeneic transfusion rate after elective surgery for thoracic arch aneurysm with deep hypothermic circulatory arrest. Twenty patients were randomized to fibrinogen concentrate ( N  = 10) or placebo ( N  = 10). The recruitment of study patients was prematurely ended due to a low inclusion rate. Perioperative transfusion, 5-minute bleeding mass after study medication and postoperative blood loss were not different between the groups with fibrinogen concentrate or placebo. Due to small volumes of postoperative blood loss and premature study termination, a beneficial effect of fibrinogen concentrate on the number of blood transfusions could not be established. However, treatment with fibrinogen efficiently restored fibrinogen levels and clot strength to preoperative values with a more effective preserved postoperative thrombin generation capacity. This result might serve as a pilot for further multicenter studies to assess the prospective significance of automated and standardized thrombin generation as a routine assay for monitoring perioperative coagulopathy and its impact on short- and long-term operative results.